Assessing the administrative challenges the use of state and local government joint account in Zaria local government - Bashir, Usman; Ismail, Mohd Mahadee; Ku Samsu, Ku Hasnita (Research and Scientific Innovation Society, 2019)
Since the introduction of joint account Zaria local government could not get access to its allocation from federation account as a result miscellaneous deductions from it allocations by Kaduna state government in the name of state and local government joint account, the situation lead to the inability of the Zaria local government for consistent payment of workers salary, gratuity and pensioners of retired local government civil servants and relegating the activities within the local government. Therefore the study attempt to identify the responses of the people on the administrative challenge fusses in Zaria local government. A phenomenological approach was used and data were obtained from purposively selected informants using semi structure interviews. Thus, thematic analysis, informal discussion and observation were employed in data analysis. The study recommends that only the abolishing of state and local government joint account Zaria local government will over power its administrative challenge.